CATALOGUE OF MAIN CHARACTERISTICS OF INDIVIDUAL PULSATION A L CYCLES OF 18 LONG-PERIODIC STARS - Marsakova, V. I.; Andronov, I. L. (Одеські астрономічні публікації, 2017)
The characteristics of individual cycles of 35 Mira-type atom are tabulated: the moments and brightness of the extreme the inverse slopes dt/dm of the light curves and corresponding error estimates. The observations for the analysis are taken from the AFOEV and VSOLJ databases for the stars: X Cam, o Cet, R Cyg, U Cyg, R Dra, T Her, RS Her. T UMa, U UMi (Mira-lype); S Aql, T Ari, V Boo, S Cam, V CVn, RS Cyg, RU Cvg, SS Vir (SRa-type); RX UMa (SRb-type)